A prospective cohort evaluation of the sensitivity and specificity of the chest X-ray for the detection of lung cancer in symptomatic adults. Issue 144 (November 2021) - Bhartia, Bobby S.K.; Hatton, Nathaniel Luke Fielding; Aslam, Rehima; Bradley, Stephen H.; Darby, Michael; Hamilton, William T.; Hurst, Emily; Kennedy, Martyn P.T.; Mounce, Luke T.A.; Neal, Richard D.; Shinkins, Bethany; Callister, Matthew E.J.
Highlights: The diagnostic accuracy of the CXR in detecting symptomatic lung cancer. A positive CXR strongly increases the probability of lung cancer being present. A negative CXR leads to a limited reduction of the probability of lung cancer. The findings allow the risk of lung cancer following a negative test to be estimated. Abstract: Background: The accuracy of the chest x-ray (CXR) in the identification of lung cancer amongst symptomatic individuals is uncertain. Purpose: To determine the diagnostic accuracy of the CXR for the detection of non-small cell carcinomas (NSCLC) and all primary intrathoracic malignancies. Methods: A prospective cohort study of consecutive CXR reports obtained within a primary care open access initiative. Eligibility criteria were symptoms specified by National Institute for Clinical Excellence as indicative of possible lung cancer and age over 50-yrs. A positive test was a CXR which led directly or indirectly to investigation with CT. The reference standards were malignancies observed within a one- or two-year post-test period. Results: 8, 948 CXR outcomes were evaluated. 496 positive studies led to a diagnosis of 101 patients with primary intrathoracic malignancy including 80 with NSCLC. Within two-years, a cumulative total of 168 patients with primary intrathoracic malignancies including 133 NSCLC were observed. The sensitivity and specificity for NSCLC were 76% (95 %CI 68–84) and 95% (95 %CI 95–96) within 1-year and 60% (95 %CI 52–69) and 95% (95 %CI 95–96) within 2-years. The 2-yr positive and negative likelihood ratios were 12.8 and 0.4. The results did not differ for NSCLC compared to all primary malignancies. Within this symptomatic population a negative test reduced the 2-year risk of lung cancer to 0.8%. Conclusions: A positive test strongly increases the probability of malignancy whereas a negative test does not conclusively exclude the disease. The findings allow the risk of malignancy following a negative test to be estimated.